SURVEY OF THE READINESS OF INSURANCE COMPANIES IN SERBIA FOR SOLVENCY II - Ilić, Mirjana; Avdalović, Veselin; Obadović, Milica (Economic Annals, 2017)
The main objective of this paper is to analyse the readiness of the largest insurance companies operating in Serbia to implement the upcoming Solvency II regulation. The survey was conducted in 2014 using a questionnaire comprising 30 questions. It was sent to the seven biggest companies operating in Serbia during the research, which cover 80% of the market. The questionnaire covered both the organizational and technical profile of the insurance companies. The survey helped to understand the benefits and problems for the domestic insurance market that would result from the introduction of the Solvency II regime and the adjustment of current legislation to the European standard, and whether the insurance sector in Serbia will manage to overcome the obstacles and adopt the policies and procedures prescribed by Solvency II when required. Adopting the European Solvency II regulation means a complete reorganization of the insurance sector in Serbia, which has not been sufficie